The Influence Of The New Curriculum On The Development Of Knowledge Of Primary School Children - Hutagalung, Debora Margaretha; Ertantinigsih, Deviani; Hikmaniar, Febriani; Avianjani, Niken Safitri; Amalina, Nur; Nurda, Nety; Habibie, Muhammad Iqbal (Institute Of Advanced Knowledge and Science, 2024)
The curriculum is the foundation of education since it acts as a road map for pupils to achieve their learning goals. Without an appropriate curriculum, students will not obtain appropriate learning targets. As time progresses, the curriculum also changes. Curriculum changes are adapted to the needs of students in their respective times. Its adaptability is critical for meeting the changing demands of students in the face of rapid technological breakthroughs and a constantly changing social context. This study investigates the advantages of building curriculum methodically in the field of education, particularly in terms of how it interacts with computer systems. The research emphasizes the need for deliberate change and calls for a planned strategy that blends technology's revolutionary potential with educational objectives. The research was conducted using the quantitative method by taking some questionnaires to the elementary school with the distribution of respondent classes, gender, hobby, extracurricular, favorite subject, dislike the subject, interest curriculum, learning methods, and homework at school. We found that the curriculum Merdeka is a new approach to developing educational curricula in Indonesia by emphasizing developing student potential with a more inclusive and creative approach.